2023
DOI: 10.1021/acsami.3c11744
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Coatings from Glassy Polyelectrolyte Complex Films

John Akintola,
Yuhui Chen,
Zachary A. Digby
et al.

Abstract: Coatings that prevent or decrease fouling are sought for many applications, including those that inhibit the attachment of organisms in aquatic environments. To date, antifouling coatings have mostly followed design criteria assembled over decades: surfaces should be well/strongly hydrated, possess low net charge, and maintain a hydrophilic character when exposed to the location of use. Thus, polymers based on ethylene glycol or zwitterionic repeat units have been shown to be highly effective. Unfortunately, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Various functionalization methods can generate zwitterionic coatings with diverse thicknesses. Zwitterionic SAMs, for instance, can have thicknesses as minimal as 1 nm. , ATRP can yield thicker coatings, reaching tens of nanometers. , Zwitterionic coatings constructed through layer-by-layer assembly can achieve thicknesses exceeding 100 nm. , Initiated chemical vapor deposition can produce zwitterionic antifouling coatings with thicknesses extending into hundreds of nanometers. , The antifouling performance of zwitterionic coatings is closely related to the coating thickness . While zwitterionic SAMs demonstrate robust resistance to protein adsorption, their sustained prevention of attachment to mammalian cells encounters challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Various functionalization methods can generate zwitterionic coatings with diverse thicknesses. Zwitterionic SAMs, for instance, can have thicknesses as minimal as 1 nm. , ATRP can yield thicker coatings, reaching tens of nanometers. , Zwitterionic coatings constructed through layer-by-layer assembly can achieve thicknesses exceeding 100 nm. , Initiated chemical vapor deposition can produce zwitterionic antifouling coatings with thicknesses extending into hundreds of nanometers. , The antifouling performance of zwitterionic coatings is closely related to the coating thickness . While zwitterionic SAMs demonstrate robust resistance to protein adsorption, their sustained prevention of attachment to mammalian cells encounters challenges.…”
Section: Resultsmentioning
confidence: 99%
“…This value overcomes 118 pN—the limiting value of the experimental setup. It is generally accepted that adsorption of the polycation at the glass surface is irreversible due to high electrostatic binding constant [ 55 , 56 , 57 ]. With the help of the optical tweezer, we have demonstrated that the interaction force could be quantified and that the electrostatic binding is not the only factor that ensures strong adhesion of the polyelectrolyte.…”
Section: Resultsmentioning
confidence: 99%